GEOCHRONOLOGY AND CORRELATION OF MESOZOIC MAGMATIC COMPLEXES IN THE NORTHERN MARGIN OF THE AMURIAN SUPERTERRANE - Sorokin A.A.; Sorokin A.P.; Ponomarchuk V.A.; Kozyrev S.K. (My University, 2004)
A subject of discussion is age of rocks in Mesozoic volcano-plutonic belts of the epi-Paleozoic Amurian superterrane. Mesozoic volcanic and intrusive complexes of the northeastern Greater Khingan and western Umlekan-Ogodzha volcano-plutonic belts are dated using the 40Ar/39Ar method of isotopic geochronology. The results obtained and dates published before are used to elaborate the correlation scheme for magmatic rocks of both belts. Similarity and distinctions in Mesozoic evolution of two structural zones under consideration are elucidated for the Late Jurassic, Early Cretaceous, and Early-Late Cretaceous boundary periods.
Keywords: Mesozoic; Mesozoic; Мезозой